What does “feasible” mean? - Joormann, Imke; Schmidt, Martin; Steinbach, Marc C.; Willert, Bernhard M. (Evaluating Gas Network Capacities, 2015)
The main goal of our efforts described in this book consists of solving the problem of validation of nominations in gas networks, i.e., deciding whether a feasible solution exists for a given set of boundary conditions represented by a nomination. However, it turns out that the meaning of “feasible” is not self-evident. This is due to a multitude of reasons, ranging from the accuracy of problem data over subtle differences between our models to tractability of optimization problems. In the current chapter we elaborate on these points and try to clarify precisely in what sense and how well the mathematical methodology presented can distinguish feasible from infeasible solutions.